Local autoimmune encephalomyelitis model in a rat brain with precise control over lesion placement - Lukasz Kalkowski; Dominika Golubczyk; Joanna Kwiatkowska; Malgorzata Domzalska; Piotr Walczak; Izabela Malysz-Cymborska (PLoS ONE, 2022)
Development of a novel, animal model for multiple sclerosis (MS) with reproducible and predictable lesion placement would enhance the discovery of effective treatments. Therefore, we would like to combine the advantages of the demyelination model with experimental autoimmune encephalomyelitis (EAE) to provide a local autoimmune encephalomyelitis (LAE) inside rat brain. We induced a demyelinating lesion by immunizing male Wistar rats, followed by blood-brain barrier opening protein (vascular endothelial growth factor) by stereotactic injection. We confirmed the immunization against myelin epitopes and minor neurological impairment. Histological assessment confirmed the lesion development after both 3- and 7 days post-injection. Our approach was sufficient to develop a demyelinating lesion with high reproducibility and low morbidity.